The intention of Egyptian healthcare workers to take the monkeypox vaccine: is urgent action required? - Ramy Mohamed Ghazy; Mai Hussein; Shymaa Mamdouh Mohamed Abdu; Doha El-sayed Ellakwa; Mahmoud M. Tolba; Naglaa Youssef; Amira Saad Mahboob; Samar Abd ElHafeez (BMC, 2024)
Abstract Background In light of the ongoing monkeypox (MPOX) epidemic, healthcare workers (HCWs) have been in contact with various diseases. Therefore, they should take appropriate preventive and control measures to maintain their health. This study assessed Egyptian HCWs' intentions to take MPOX vaccines. Methods A cross-sectional survey was conducted using social media platforms between September 27 and November 4, 2022. An anonymous online survey using the 5C scale was conducted using convenience and snowball sampling methods to assess the five psychological antecedents of vaccination (i.e., confidence, constraints, complacency, calculation, and collective responsibility). Results A total of 399 HCWs with a mean age of 32.6 ± 5.7 participated in this study. Of them, 89.7% were female. The five C psychological antecedents of vaccination were as follows: 55.9% were confident about vaccination, 50.6% were complacent, 56.6% experienced constraints, 60.7% calculated the risk and benefit, and 58.4% had collective responsibility. Multivariate analysis showed that high income level and having information about MPOX were significant predictors of confidence in the MPOX vaccines (adjusted odds ratio ((AOR) = 4.19, 95% CI (1.12- 15.59), P = 0.032). Participants aged 31-45 years and 19-30 years showed significant association (AOR = 2.46, 95% CI (0.85-7.15), P = 0.096) and (AOR = 4.19, 95% CI (1.39-12.64), P = 0.011), respectively. Having an idea about the MPOX vaccines significantly predicted the complacency domain (AOR = 3.77, 95%CI (1.47-9.65, P = 0.006). Moreover, precollege/undergraduate education and having an idea about MPOX vaccination were significant predictors of the constraint domain (AOR = 1.81.95% CI (1.09-2.99, P = 0.020), (AOR = 2.70, 95% CI (1.05-6.95, P = 0.038), respectively). Female sex, having a diploma, postgraduate studies, and having an idea about MPOX vaccine significantly predicted calculation domain (AOR = 2.06, 95% CI (1.05-4.04, P = 0.035), (AOR = 3.98,95% CI (1.33-11.87, P = 0.013), (AOR = 2.02, 95% CI (1.25-3.26, P = 0.004) & (AOR = 2.75. 95% CI (1.05-7.18, P = 0.039), respectively. The only significant predictor of collective responsibility was having a diploma and postgraduate studies (AOR = 3.44, 95% CI (1.21-9.78, P = 0.020), (AOR = 1.90,95% CI (1.17-3.09, P = 0.009). Conclusions Efforts to control MPOX should focus on promoting protective measures such as the vaccination of HCWs as well as raising their awareness about the updated information regarding the virus and the approved vaccines.